Levantamento e caracterização de poços subterrâneos na zona urbana do município de Rafael Fernandes-RN - Rodrigues, Jéssica Ferreira (Universidade Federal Rural do Semi-Árido, 2019)
Since 2012, the northeastern region of the country has been experiencing a considerable period of drought. During this period, the region in which the municipality is located has been affected by the scarcity of water. Thus, one of the alternatives that may have been used by the population in order to mitigate the consequences of drought is the excavation of underground wells destined for the abstraction of groundwater. The present work aimed to perform a survey and characterization of the wells destined to the abstraction of groundwater, being these located in the urban zone of the city of Rafael Fernandes - RN. For collection of data, an exploratory and descriptive research was carried out, aiming to carry out a survey and characterization of the wells found in the urban area of the municipality, and this characterization sought to collect information on physical characteristics (depth of well digging, flow, among others), of consumption and environmental presented by each well, and also sought to acquire some knowledge about how the municipality's city water resources management is carried out. It was observed from the application of the research methods that 93.75% of the wells located in the urban area of the municipality are deep tubular wells, while only 6.25% are wells called shallows, in the cases analyzed amazon wells, besides it has been found that some of the wells have a deficiency when related to the presence of certain elements that become essential to the well, such as protection covers, protective slab, filter, among others. With regard to the management of groundwater resources in the city, a deficit related mainly to the monitoring of the potability of the water consumed by the population is observed. This way, a deficiency related to the requirements expressed by the legislation in force when related to the project and execution of the analyzed wells is verified, especially when analyzing Questions aimed at guaranteeing the quality of these waters.
Keywords: Recursos hídricos; Potabilidade; Água subterrânea; NBR 12212; Water resources; Potability; Underground water; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA